Transoral Laser Microsurgery for Supraglottic Cancer - Ambrosch, Petra; Gonzalez-Donate, Mireia; Fazel, Asita; Schmalz, Claudia; Hedderich, Jürgen (Frontiers in Oncology, 2018)
ABSTRACT Introduction Transoral laser microsurgery (TLM) represents one of the most effective treatment strategies for supraglottic carcinomas. Early supraglottic carcinoma has excellent outcomes independently of the treatment approach. The role of TLM for the treatment of locally advanced tumors is debated. Particularly, the functional outcomes after TLM are still to be validated on larger cohorts of patients. This study analyzes the oncologic and functional outcomes after TLM for supraglottic carcinomas. Patients and methods Ninety-one patients with pT1-pT4a supraglottic carcinomas treated between 01/2002 and 12/2012 were analyzed. Distribution of tumors (UICC 2010) was 11 patients with pT1, 31 with pT2, 36 with pT3 and 13 with pT4a tumors. Node status was positive in 40 (43.6%) patients; 61 (67.1%) had stage III or IV disease. Local control and survival were estimated using the Kaplan-Meier method. For the assessment of functional outcomes, the MD Anderson Dysphagia Inventory (MDADI), the Voice Handicap Index-10 (VHI) and the performance status scale for head and neck cancer (PSS-HN) were used. Results Median age was 62 years (range, 33-88 years). Fourteen (15.4%) patients developed a local or locoregional recurrence. The 5-years local control rate and 5-years ultimate local control rate was 72% and 92%, respectively. The 5-years overall survival rate was 63%. Twelve (13.2%) patients needed temporary tracheostomy. Sixty-eight (74.0%) patients had a nasogastric feeding tube postoperatively. At one year postoperative follow-up only three patients were PEG dependent. The median VHI-10 score was 35, the median MDADI composite score was 80, and the median score of the domain ‘normalcy of diet’ in the PSS-HN was 91. Conclusion The oncologic outcomes are comparable to the results of open surgery for early and advanced supraglottic carcinomas. Functional swallowing outcome is superior to open surgery and to concomitant chemoradiation. Patients treated with TLM perceive low levels of voice- and swallowing-related quality of life impairment.